DIPLOMASI KESEHATAN TIONGKOK DALAM PENANGGULANGAN PANDEMI COVID-19 DI ETHIOPIA PADA TAHUN 2020-2023 - K.Sh, Latifah; Olivia, Yessi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
The COVID-19 pandemic transformed global health dynamics and international relations, particularly in developing countries like Ethiopia. China actively engaged in health diplomacy in Ethiopia during the pandemic, connected to its broader Belt and Road Initiative (BRI) strategic interests in the region. This research analyzes China's health diplomacy in Ethiopia during 2020-2023 and examines its relationship with BRI programs in the country. This research employed a qualitative methodology using document analysis as the primary data collection technique and applied Ilona Kickbusch's global health diplomacy theoretical framework. Various document sources were analyzed including government reports, international organization publications, academic journals, news articles, and policy documents related to China's health diplomacy in Ethiopia. The analysis focused on examining China's health assistance programs, vaccine diplomacy, medical aid, and health infrastructure development conducted in Ethiopia during the research period. Research findings indicate that China's health diplomacy in Ethiopia during the COVID-19 pandemic aligned strategically with BRI objectives. China provided substantial medical assistance including vaccine donations, medical equipment supplies, and health facility construction. These activities strengthened bilateral relations, enhanced China's presence in Ethiopia's health sector, and supported broader BRI goals in East Africa. The study concludes that health diplomacy has become an important instrument in China's foreign policy strategy in regions strategic to BRI success. Keywords: China's health diplomacy, COVID-19 pandemic, Ethiopia, Belt and Road Initiative, bilateral relations, vaccine diplomacy